Penerapan Model Pembelajaran Kooperatif Group Investigasi untuk Meningkatkan Hasil Belajar dan Kemampuan Berpikir Kritis - Pahrurrozi Pahrurrozi (Jurnal Penelitian dan Pengkajian Ilmu Pendidikan: e-Saintika, 2019)
[Title: The Implementation of the Cooperative Group Investigative Learning Model to Improve Learning Outcomes and Critical Thinking Ability]. The critical thinking ability is one of the abilities students must-have in the 21st century that is oriented to the processing of information based on the results of the reflective analysis to determine what to believe and to do. The results of a series of observations and case studies note that the critical thinking ability of class X3 students of SMA Negeri 5 Malang is still low. This study aims to improve student learning outcomes and critical thinking skills through the application of an investigative cooperative group learning model. This research is a lesson study research with the steps plan, do, see. The subjects of this study were the students of class X3 of SMAN 5 Malang, totalling 36 students with teaching materials about fungi. Test instruments, observation sheets, and student worksheets are used to obtain data on learning outcomes and students' critical thinking ability in this study. The results showed an increase in student learning outcomes in cycle 1 amounted to 69.7 and cycle 2 amounted to 76.1. Critical thinking ability of students has increased in cycle 1 by 84.5 and in cycle 2 by 90.5. Based on the results of the study it can be concluded that interactive and collaborative learning activities which in this study use a cooperative group investigation model can improve learning outcomes and critical thinking ability of class X3 students of SMAN 5 Malang.